Factors Associated with the Use of Skilled Birth Attendants in Indonesia - Jamil, Siti Nurhasiyah; Octavia, Eva Nur; Fadliah, Balqis Nur; Gandirawati, Elsa Maudi (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
The maternal mortality rate in Indonesia of 305/100,000 live births is still far from the SDGs target in the year 2030, which is 70/100,000 live births. The WHO states that the main causes of maternal mortality are bleeding, infection, preeclampsia-eclampsia, complications of childbirth, and unsafe abortion. This can be prevented if the mother can access health services, especially the use of skilled birth attendants to overcome complications of pregnancy and childbirth. This study aims to determine the factors associated with the use of skilled birth attendants in Indonesia. This cross-sectional study with a total sample of 4.543 women aged 15-49 years who gave birth to the last child selected in a sample of secondary data Indonesia Demographic Health Survey (IDHS) 2017. The dependent variable of the study was a skilled birth attendants and the independent variable was sociodemographic factors (age, education, employment, area of residence), antenatal factors (antenatal care examiner, antenatal place, antenatal frequency), medical factors (pregnancy complications and birth complications). The results of this study indicate that the dominant factor in the selection of skilled birth attendants is pregnancy examiners. Pregnancy examiners who examine the pregnancy by an obstetrician have the opportunity to choose a permanent delivery at an obstetrician, which is 8.33 (95% CI 6,75 – 10,29) times compared to choosing a midwife after being controlled by other variables.